1994
DOI: 10.1103/physrevb.49.4850
|View full text |Cite
|
Sign up to set email alerts
|

Observations of coverage- and temperature-dependent surface structures formed upon Li deposition on Cu(110)

Abstract: A systematic study of surface structures of was performed by means of low-energy electron-diffraction (LEED) and Auger electron spectroscopy techniques. The experiments were carried out with increasing deposition of Li both at low temperature (90 K) and room temperature (300 K). At 90 K a series of LEED patterns, (3 X 1), (2 X 1), (3 X 1), and successive complicated structures were observed with increasing Li coverage. The sequence of the LEED patterns was interpreted as simple overlayer structures of Li in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…We also tested the adsorption energy of Li at high coverage, and found that the hol site was still the most preferred site. Our findings are in agreement with Nakanishi et al's investigation with the help of LEED and AES techniques [4]. For the adsorption of lbri sites at both coverages, the energies are found to be about 0.1 eV less stable than the hol sites.…”
Section: Adsorption Of LI On Cu(1 1 0) Surface At Low Coveragesupporting
confidence: 95%
See 4 more Smart Citations
“…We also tested the adsorption energy of Li at high coverage, and found that the hol site was still the most preferred site. Our findings are in agreement with Nakanishi et al's investigation with the help of LEED and AES techniques [4]. For the adsorption of lbri sites at both coverages, the energies are found to be about 0.1 eV less stable than the hol sites.…”
Section: Adsorption Of LI On Cu(1 1 0) Surface At Low Coveragesupporting
confidence: 95%
“…It is indicated that the rumpling between the planes defined by atoms of Li and Cu in the 1st-layer has been formed. Using LEED, Nakanishi et al also proposed that surface alloys similar to those observed on Cu(0 0 1) surface were formed on the present Cu(1 1 0) surface [4]. They found that at low temperatures Li overlayers were formed on Cu surfaces, while at room temperature intermixed layers of Li and Cu were formed.…”
Section: Adsorption Of LI On Cu(1 1 0) Surface At Low Coveragementioning
confidence: 87%
See 3 more Smart Citations